2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin suppress AChE activity in NGF treated PC12 cells. (25th November 2016) - Xu, Li; Chen, Yangsheng; Xie, Heidi Q.H.; Xu, Tuan; Fu, Hualing; Zhang, Songyan; Tsim, Karl W.K.; Bi, Cathy W.C.; Zhao, Bin
Abstract: PC12 is a well studied cell model for neuronal differentiation. AChE is also considered as a marker for neuronal differentiation. In this study, we detected the change of AChE activity during the NGF induced differentiation of PC 12 cells, and targeted on the ratio of the activity of AChE on the cell surface, and found that NGF mainly increased the intracellular AChE activity. Dioxin is a kind of persistent organic pollutants which have extreme impact on human health and widely distributed all over the world. Recently, AChE was reported as a target of the toxicity of dioxin. Here we investigated the effect of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) on AChE activity in the PC12 cells, and found that at the later stage of differentiation, TCDD could decrease the AChE activity. This down regulation might not related to transcriptional regulation. Highlights: Dioxin could depress AChE activity during NGF induced differentiation in PC12 cells. Dioxin might primarily affect the activity of intracellular forms of AChE. At transcriptional level, dioxin did not regulate expression of AChE gene.